STAR: A consensus for skin tear classification. - Carville, Keryln; Lewin, Gill; Newall, Nelly; Haslehurst, P.; Michael, Rene; Santamaria, Nick; Roberts, Pamela (Cambridge Publishing, 2007)
Until now the Payne-Martin Classification System for Skin Tears has been the only skin tear classification system reported in the literature. Considering that the development of this taxonomy began over twenty years ago, it is rather puzzling that it has been poorly utilised in Australia. especially in light of the fact that skin tears are perceived to be common wounds amongst frail older or disabled persons 1, 2, 3 and their prevalence can be expected to escalate in line with our ageing population. Stage one of the Skin Tear Audit Research (STAR) study aimed to gain a consensus from Australian nurse experts in wound management on a classification system for skin tears and to test the reliability of the resulting classification system. This paper reports on the processes undertaken to achieve a consensus, the STAR Skin Tear Classification System that resulted, and the reliability testingthat it underwent.